Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Karyawan - Tjandra Tirtono; Muhammad Ulinnuha (Jurnal Ilmiah Aset, 2017)
The purpose of this research was to describe and analyze the influence of individual factor, social factor, and main factor in work on job satisfaction of employee in Koperasi Esgeef-878 Semarang. The research hypothesis was the individual factor, social factor, and main factor in work had positive significant effect on job satisfaction of employee in Koperasi Esgeef-878 Semarang. The sample were 35 employees of Koperasi Esgeef-878 Semarang obtained by population study. The data were obtained using a questionnaire, which was then analyzed using multiple linier regression analysis with SPSS version 22.00 for Windows. The result research was regression model Y = -4,232 + 0,467X1+ 0,405X2+ 0,423X3. Hypotesis test results showed individual factor, social factor, and main factor in work had positive significant effect on job satisfaction of employee in Koperasi Esgeef-878 Semarang both partial and simultant.